Operational Audit as a Performance Assessment Tool of Front Office Cashier at Renaissance Bali Uluwatu Resort & Spa - N L P E Kartikayeni; I N Subratha; I M M Arsana (Journal of Applied Sciences in Accounting, Finance, and Tax, 2020)
An operational audit is an examination conducted to review (systematically) part or all of the organization's activities in order to evaluate whether the available resources have been used effectively and efficiently. The front office cashier is one of the most important parts because it has the main function of carrying out tasks related to guest account payments at check-in and check-out related to the hotel's main source of revenue. Payment transaction processes and reports on transactions made must comply with applicable Standard Operating Procedures. This study aims to analyze and reveal the performance of the front office cashier related to payment transactions made by guests during check-in and check-out at the Renaissance Bali Uluwatu Resort & Spa. The data used in this research comes from primary data obtained by conducting interviews and documentation. The analysis technique used is the Miles and Huberman analysis technique, where the activities in qualitative data analysis are carried out interactively and continue to completion, so that the data is saturated. The results of the operational audit on the cashier's front office performance is the front office cashier's performance is considered to be efficient but less effective. This can be seen from the frequent occurrence of shortcomings when reporting, namely the attached transaction proof in the form of a credit card slip, which based on the SOP should also be attached to the cashier's journal report submitted to the Finance Department